Examining teacher roles and competences in Content and Language Integrated Learning (CLIL) - Pavón Vázquez, Víctor; Ellison, Maria (Linguarum Arena, 2018)
Content and Language Integrated Learning (CLIL) is increasingly widespread in educational institutions of all levels and sectors across Europe. Thanks to a burgeoning research base and subsequent publications, we are now, more than ever, in a position to confidently testify to the benefits of CLIL as a successful educational approach for this day and age. However, the popularity of CLIL should not be mistaken for something that is easy to implement and deliver. As with many an innovation, demand or desire to jump on the bandwagon often outweigh resources, which in the case of CLIL means teachers who possess appropriate levels of linguistic competence in the foreign language and knowledge of the subject specialism. Equally important is the need to adapt teaching methodology to cater for the integrated learning of both content and language. This entails a change in perspective about the foreign language as a subject to that of a tool in content learning. This paper addresses teacher roles and methodology in CLIL contexts and highlights the importance of teacher education for CLIL.